BUDAYA KONSUMSI BAJU COUPLE PADA RESEPSI PERNIKAHAN PERNIKAHAN DI KABUPATEN SUMBAWA DENGAN VARIABEL MEDIASI ONLINE SHOPPING CONVENIENCE - Santoso, Agus; Purnama, Yuni; Ismiyarti, Wilia (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study analyzes the consumption culture of couple clothing at wedding receptions in Sumbawa Regency by incorporating online shopping convenience as a mediating variable. It examines the effects of consumption culture, social currency, and Digital Marketing on purchasing decisions, and the mediating role of online shopping convenience. A quantitative explanatory research design was employed. Primary data were collected through an online questionnaire using a nonprobability purposive sampling technique, involving 135 respondents who had purchased or used couple clothing for wedding receptions. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that consumption culture and Digital Marketing have a positive and significant effect on online shopping convenience, while social currency has an adverse effect with limited significance. Online shopping convenience significantly influences purchasing decisions and mediates the effects of consumption culture and Digital Marketing . However, social value did not significantly influence purchase decisions and did not mediate the effect of online shopping convenience. The dominance of cash-on-delivery (COD) payment methods and spending under IDR 200,000 indicates that purchase decisions are driven more by functional considerations and transaction convenience than by social image. These findings highlight the dominant role of cultural values ??and online convenience in shaping couples' clothing purchase decisions.